Genetic integrity is still maintained in natural populations of the indigenous wild apple species Malus sylvestris (Mill.) in Saxony as demonstrated with nuclear SSR and chloroplast DNA markers. Issue 20 (28th September 2020) - Reim, Stefanie; Lochschmidt, Frank; Proft, Anke; Höfer, Monika
Abstract: Malus sylvestris (Mill.) is the only indigenous wild apple species in Central Europe. Agriculture, forestry, and urbanization increasingly endanger Malus sylvestris natural habitats. In addition, the risks of cross‐hybridization associated with increase in the cultivation of the domesticated apple Malus × domestica (Borkh.) threaten the genetic integrity of M. sylvestris . The present study investigated the number of hybrids, genetic diversity, and genetic structure of 292 putative M. sylvestris that originate from five different natural M. sylvestris populations in Saxony, Germany. All samples were genetically analyzed using nine nuclear microsatellite markers (ncSSR) and four maternally inherited chloroplast markers (cpDNA) along with 56 apple cultivars commonly cultivated in Saxony. Eighty‐seven percent of the wild apple accessions were identified as pure M. sylvestris . The cpDNA analysis showed six private haplotypes for M. sylvestris, whereas three haplotypes were present in M. sylvestris and M. × domestica . The analysis of molecular variance (AMOVA) resulted in a moderate (ncSSR) and great (cpDNA) variation among pure M. sylvestris and M. × domestica individuals indicating a low gene flow between both species. The genetic diversity within the pure M. sylvestris populations was high with a weak genetic structure between the M. sylvestris populations indicating an unrestricted genetic exchange between these M. sylvestris populations. The clear distinguishing of M. sylvestris and M. ×domestica confirms our expectation of the existence of pure M. sylvestris accessions in this area and supports the argument for the implementation of preservation measures to protect the M. sylvestris populations in Saxony. Abstract : The present study investigated the number of hybrids, genetic diversity, and genetic structure of 292 putative M. sylvestris that originate from five different natural populations in Saxony, Germany. Genetic analysis were performed with nuclear and chloroplast markers. We detected a high genetic diversity within the pure M. sylvestris populations but with a weak genetic structure between the M. sylvestris populations indicating an unrestricted genetic exchange between these M. sylvestris populations.